Clinical criteria for COVID-19-associated hyperinflammatory syndrome: a cohort study. (December 2020) - Webb, Brandon J; Peltan, Ithan D; Jensen, Paul; Hoda, Daanish; Hunter, Bradley; Silver, Aaron; Starr, Nathan; Buckel, Whitney; Grisel, Nancy; Hummel, Erika; Snow, Gregory; Morris, Dave; et al.
Summary: Background: A subset of patients with COVID-19 develops a hyperinflammatory syndrome that has similarities with other hyperinflammatory disorders. However, clinical criteria specifically to define COVID-19-associated hyperinflammatory syndrome (cHIS) have not been established. We aimed to develop and validate diagnostic criteria for cHIS in a cohort of inpatients with COVID-19. Methods: We searched for clinical research articles published between Jan 1, 1990, and Aug 20, 2020, on features and diagnostic criteria for secondary haemophagocytic lymphohistiocytosis, macrophage activation syndrome, macrophage activation-like syndrome of sepsis, cytokine release syndrome, and COVID-19. We compared published clinical data for COVID-19 with clinical features of other hyperinflammatory or cytokine storm syndromes. Based on a framework of conserved clinical characteristics, we developed a six-criterion additive scale for cHIS: fever, macrophage activation (hyperferritinaemia), haematological dysfunction (neutrophil to lymphocyte ratio), hepatic injury (lactate dehydrogenase or asparate aminotransferase), coagulopathy (D-dimer), and cytokinaemia (C-reactive protein, interleukin-6, or triglycerides). We then validated the association of the cHIS scale with in-hospital mortality and need for mechanical ventilation in consecutive patients in the Intermountain Prospective Observational COVID-19 (IPOC) registry who were admitted to hospital with PCR-confirmed COVID-19. We used a multistate model to estimate the temporal implications of cHIS. Findings: We included 299 patients admitted to hospital with COVID-19 between March 13 and May 5, 2020, in analyses. Unadjusted discrimination of the maximum daily cHIS score was 0·81 (95% CI 0·74–0·88) for in-hospital mortality and 0·92 (0·88–0·96) for mechanical ventilation; these results remained significant in multivariable analysis (odds ratio 1·6 [95% CI 1·2–2·1], p=0·0020, for mortality and 4·3 [3·0–6·0], p<0·0001, for mechanical ventilation). 161 (54%) of 299 patients met two or more cHIS criteria during their hospital admission; these patients had higher risk of mortality than patients with a score of less than 2 (24 [15%] of 138 vs one [1%] of 161) and for mechanical ventilation (73 [45%] vs three [2%]). In the multistate model, using daily cHIS score as a time-dependent variable, the cHIS hazard ratio for worsening from low to moderate oxygen requirement was 1·4 (95% CI 1·2–1·6), from moderate oxygen to high-flow oxygen 2·2 (1·1–4·4), and to mechanical ventilation 4·0 (1·9–8·2). Interpretation: We proposed and validated criteria for hyperinflammation in COVID-19. This hyperinflammatory state, cHIS, is commonly associated with progression to mechanical ventilation and death. External validation is needed. The cHIS scale might be helpful in defining target populations for trials and immunomodulatory therapies. Funding: Intermountain Research and Medical Foundation.